Aplicación del poster científico como herramienta didáctica, para fortalecer el aprendizaje de los tejidos vegetales, en la asignatura de ciencias naturales con los estudiantes del noveno grado paralelo “e” del colegio de bachillerato 27 de febrero sección vespertina, de la ciudad de Loja, periodo 2014- 2015 - Merino Sanchez, Nixon Fernando (2017)
The importance of applying the “scientific poster” as a didactic tool to strengthen learning in the area of Natural Sciences, it is to graphically represent any topic and contribute to the strengthening of visual learning of plant tissues. The present research aimed at the APPLICATION OF THE SCIENTIFIC POSTER AS A TEACHING TOOL TO STRENGTHEN THE LEARNING OF VEGETABLES TISSUES IN THE SUBJECT OF NATURAL SCIENCES WITH THE STUDENTS OF 9th GRADE HIGH SCHOOL, COURSE "E" FROM “27 DE FEBRERO “ HIGH SCHOOL, AFTERNOON SECTION, FROM LOJA CITY. ACADEMIC PERIOD 2014-2015, as a general objective: to apply the scientific poster as a didactic tool, to strengthen the learning of plant tissues, in the Natural Science Subject with the students of the 9th grade high school, course"E" from "27 de Febrero" high school. The following methods were applied in the development of this research: analytical-synthetic method, transversal, quasi-experimental, inductive, statistical, workshop and deductive, The data was obtained by applying the informal direct observation technique and a survey. A total of 17 students were surveyed. As a result, it was possible to determine through the data collection from the surveys that 9th grade high school students from "27 de Febrero" High School, that they do not have a clear idea about the definition, classification, and importance of the vegetal tissues. They do not identify the types of cells that form these kinds of tissues. It seems, that the lack of didactics tools are not allowing strengthen learning in these topics. Therefore, as a suggestion educational authorities have to organize workshops, seminars and trainings in the development and design of didactic tools, focus on the subject of Natural Sciences, with the purpose to facilitate the teaching-learning process. Following the same idea, the students of 9th grade high school from "27 de Febrero" High School, suffer a low level of learning in the topic of “vegetables tissues”, because of the lack of put on practice didactics tools such as the “didactic poster” in the class in order to strengthen the learning. As a recommendation, it suggested to use the scientific poster as a didactic tool to enhance and stimulate learning, concerning “vegetables tissues” facilitating visual learning in students.